Prevalence of pain and its associated factors among the oldest-olds in different care settings – results of the AgeQualiDe study - Tina Mallon; Annette Ernst; Christian Brettschneider; Hans-Helmut König; Tobias Luck; Susanne Röhr; Siegfried Weyerer; Jochen Werle; Edelgard Mösch; Dagmar Weeg; Angela Fuchs; Michael Pentzek; et al. (BMC Family Practice, 2018)
Abstract Background The prevalence of pain is very common in the oldest age group. Managing pain successfully is a key topic in primary care, especially within the ageing population. Different care settings might have an impact on the prevalence of pain and everyday life. Methods Participants from the German longitudinal cohort study on Needs, Health Service Use, Costs and Health-related Quality of Life in a large Sample of Oldest-old Primary Care Patients (85+) (AgeQualiDe) were asked to rate their severity of pain as well as the impairment with daily activities. Besides gender, age, education, BMI and use of analgesics we focused on the current housing situation and on cognitive state. Associations of the dependent measures were tested using four ordinal logistic regression models. Model 1 and 4 consisted of the overall sample, model 2 and 3 were divided according to no cognitive impairment (NCI) and mild cognitive impairment (MCI). Results Results show a decline in pain at very old age but nonetheless a high prevalence among the 85+ year olds. Sixty-three per cent of the participants report mild to severe pain and 69% of the participants mild to extreme impairment due to pain with daily activities. Use of analgesics, depression and living at home with care support are significantly associated with higher and male gender with lower pain ratings. Conclusions Sufficient pain management among the oldest age group is inevitable. Outpatient care settings are at risk of overlooking pain. Therefore focus should be set on pain management in these settings.